Contemporary Ross procedure outcomes: medium- to long-term results in 214 patients. (9th May 2021) - Generali, T; Jansen, K; Steedman, R; De Rita, F; Viganò, G; McParlin, D; Hermuzi, A; Crossland, D; O'Sullivan, J; Coats, L; Hasan, A; Nassar, M S
Abstract:  : OBJECTIVE: Our goal was to present 2 decades of our experience with the Ross procedure and its sequential modifications, adopted since 2010, to improve the reoperation rate. METHODS: We performed a single-centre, retrospective review of database information and medical notes about the implantation technique: the freestanding root. We compared era 1 (1997–2009) and era 2 (2010–2019). RESULTS: Between 1997 and 2019, a total of 214 Ross procedures were performed (71% men, median age 24 years) [interquartile range (IQR) 15–38]. Of these, 87% had various forms of congenital-dysplastic aortic valves. The median cross-clamping and bypass times were 173 (IQR 148–202) and 202 (IQR 182–244) min. The median postoperative stay was 6 days (2–77). Thirty-day mortality was 0.5%. The median follow-up time was 8.2 years (IQR 3.9–13.2). Survival at 10 and 20 years was 97% and 95%; freedom from greater than moderate aortic regurgitation or aortic valve intervention was 91% and 80%; and 93% of the patients were in New York Heart Association functional class I. Twenty (21%) patients operated on during era 1 and 6 (9%) during era 2 underwent autograft reoperations. The median follow-up time was 14.3 (IQR 11.5–17.4) and 4.8 (IQR 2.5–7) years. Freedom from autograft reoperation was 87% and 69% at 10 and 20 years, with no significant difference between eras. Freedom from homograft reoperation was 96% and 76% at 10 and 20 years. The presence of aortic regurgitation, infective endocarditis and era 1 were predictors of autograft reoperation. Male gender and era 1 were predictors of neoaortic root dilatation. CONCLUSIONS: The contemporary modified Ross procedure continues to deliver excellent results and should remain part of the strategy to treat children and young adults requiring aortic valve replacement.